2019
DOI: 10.15578/jppi.24.4.2018.283-297
|View full text |Cite
|
Sign up to set email alerts
|

Komposisi Jenis, Hasil Tangkapan Per Upaya, Musim Dan Daerah Penangkapan Ikan Hiu Di Perairan Samudera Hindia Selatan Jawa

Abstract: Penangkapan hiu di Indonesia setiap tahun meningkat jumlahnya sehingga diperlukan penelitian agar pemanfaatannya lestari. Penelitian ini bertujuan mengkaji komposisi jenis, hasil tangkapan per upaya, musim dan daerah penangkapan ikan hiu. Penelitian dilaksanakan pada tahun 2015-2016 di Pelabuhan Perikanan Samudera Cilacap, Jawa Tengah. Penelitian dilakukan dengan metode survey dan pengumpulan data bulanan dibantu oleh enumerator. Hasil penelitian menunjukkan komposisi jenis ikan hiu yang tertangkap di perairan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Then their presence is relatively strongly influenced by the strength or weakness of the current speed. Research (Priatna et al 2010) reveals that the aggregation pattern of small pelagic fish tends to be in front of FADs against currents, so understanding this can make it easier to catch fish. A flock movement of schooling of fish will rather ease to catch fish than fish that move with irregular movement pattern.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Then their presence is relatively strongly influenced by the strength or weakness of the current speed. Research (Priatna et al 2010) reveals that the aggregation pattern of small pelagic fish tends to be in front of FADs against currents, so understanding this can make it easier to catch fish. A flock movement of schooling of fish will rather ease to catch fish than fish that move with irregular movement pattern.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the findings (Doray et al 2007), monitoring of fish schooling in FAD areas using echo-sounding techniques, underwater cameras and fishing to assess the aggregation structure of fish during the day showed that small pelagic fish with a FL size of 12 cm was at a depth of 10-30 meters. Then FL fish with a size of 30 meters were caught at a depth of 0-20 meters, whereas according to (Priatna et al 2010), the highest density in the FAD area was found in the surface layer to a depth of 25 m and (Taquet 2004), from a few small individual fishes located just below the FAD visually observed by diver range 0 to 30 meters, maximum 50 meters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high consumer interest in fish makes fishermen catch large numbers continuously, regardless of their conservation status (Nugraha et al, 2020;Rizal et al, 2017). Many protected fish species are still caught by fishermen and then distributed to restaurants around the coast, especially sharks (Permana & Kusuma Pringgo, 2020;Prihatiningsih & Chodriyah, 2019). Therefore, this study aims to identify the conservation status of marine biota sold in restaurants in Pangandaran Regency.…”
Section: Introductionmentioning
confidence: 99%